Kinerja Maqashid Syariah dan Financial Sustainability Bank Umum Syariah di Indonesia - Ari Sita Nastiti; Moh. Halim (Jurnal Eksplorasi Akuntansi, 2024)
Research on the relationship between maqashid sharia performance and financial sustainability of Islamic banks in Indonesia is still rare. Research related to the effect of performance on financial sustainability of Islamic banks mostly uses CAMEL ratio analysis which only emphasizes financial performance. This study aims to examine the relationship between maqashid sharia performance and financial sustainability of Islamic Commercial Banks in Indonesia. This research uses quantitative methods with multiple regression analysis techniques. The research sample is 58 data from 12 Islamic Commercial Banks registered on OJK in 2016 - 2020. The results showed that IMS had a significant negative effect on FSR. These results indicate that the higher the maqashid sharia performance achieved, it actually causes a decrease in financial sustainability as measured by the Financial Sustainability Ratio of the Islamic bank. Future research is expected to not only test the factors that affect the financial sustainabilty of Islamic banks, but also other types of Islamic entities.